2008
DOI: 10.1080/00016480801965019
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for adductor spasmodic dysphonia – efficacy of bilateral thyroarytenoid myectomy under microlaryngoscopy

Abstract: The constriction was eliminated immediately after surgery and the patients became capable of smooth phonation. Hoarseness was recognized, but it began to ease after 1-2 months and was corrected to B grade 1-0 of the GRBAS scale approximately 6 months after the surgery. Improvement in the condition was noted in all seven patients according to evaluations based on the mora method. All patients are currently in the B grade 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 18 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…1,5 As the etiology still remains unknown, the so far proposed treatment for ADSD are directed to the neuromuscular site, intending to eliminate the abnormal neural impulse or the spasm and hyperactivity of the involved muscles, such as surgery to laryngeal innervation, 6-10 chemical denervation of the thyroarytenoid muscle by botulinum toxin injection, 11 laryngeal framework surgery such as type II 3,12 and type III 13,14 thyroplasty, and partial myectomy of the thyroarytenoid muscle. 15,16 Vocal therapy is inefficient in the treatment of spasmodic dysphonias, especially in moderate and severe cases. 17 At the moment, botulinum toxin injection is considered to be the first-choice therapy by most services 18,19 mainly because of excellent vocal outcome obtained and its easy application.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 As the etiology still remains unknown, the so far proposed treatment for ADSD are directed to the neuromuscular site, intending to eliminate the abnormal neural impulse or the spasm and hyperactivity of the involved muscles, such as surgery to laryngeal innervation, 6-10 chemical denervation of the thyroarytenoid muscle by botulinum toxin injection, 11 laryngeal framework surgery such as type II 3,12 and type III 13,14 thyroplasty, and partial myectomy of the thyroarytenoid muscle. 15,16 Vocal therapy is inefficient in the treatment of spasmodic dysphonias, especially in moderate and severe cases. 17 At the moment, botulinum toxin injection is considered to be the first-choice therapy by most services 18,19 mainly because of excellent vocal outcome obtained and its easy application.…”
Section: Introductionmentioning
confidence: 99%
“…However, the situation is different in Japan, where injection of botulinum toxin is not covered by the Japanese National Health Insurance; for example, even spasmodic dysphonia is treated by surgery in Japan. 10,14,15 Therefore, in Japan, botulinum toxin is not used in the treatment of mutational dysphonia.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical treatment is irreversible and, in consequence, has the advantage of maintaining the long-term positive effect. Studies have shown that the TA muscle does not regenerate after resection 12 .…”
Section: Myectomymentioning
confidence: 99%
“…The results presented were positive in most cases and the scholars stressed the irreversibility of the surgery [12][13][14]33 . Regarding selective laryngeal adductor denervation and reinnervation surgery, two articles from the same group of researchers were found.…”
Section: Injection Of Btmentioning
confidence: 99%